Neonatal maternal separation stress elicits lasting DNA methylation changes in the hippocampus of stress-reactive Wistar Kyoto rats - McCoy, Chelsea R. (Eur J Neurosci, 2016)
Early-life stress (ELS) can alter neurodevelopment in variable ways, ranging from producing deleterious outcomes to stress resilience. While most ELS studies focus on its harmful effects, recent work by our lab and others shows that ELS elicits positive effects in certain individuals. We exposed Wistar-Kyoto (WKY) rats, known for a stress reactive, anxiety-/depression-like phenotype, to maternal separation (MS), a model of ELS. MS exposure elicited anxiolytic and antidepressant behavioral effects as well as improved cardiovascular function in adult WKY offspring. The present study interrogates an epigenetic mechanism (DNA methylation) that may confer the adaptive effects of MS in WKY offspring. We quantified global genome methylation levels in limbic brain regions of adult WKYs exposed to daily 180-min MS or neonatal handling from postnatal day 1–14. MS exposure triggered dramatic DNA hypermethylation specifically in the hippocampus. Next-generation sequencing methylome profiling revealed reduced methylation at intragenic sites within two key nodes of insulin signaling pathways: the insulin receptor and one of its major downstream targets, mitogen activated protein kinase kinase kinase 5 (Map3k5). We then tested the hypothesis that enhancing DNA methylation in WKY rats would elicit adaptive changes akin to the effects of MS. Dietary methyl donor supplementation improved WKY rats’ anxiety/depression-like behaviors and also improved cardiovascular measures, similar to previous observations following MS. Overall these data suggest a potential molecular mechanism that mediates a predicted adaptive response whereby ELS induces DNA methylation changes in the brain that may contribute to successful stress coping and adaptive physiological changes in adulthood.